Fostering Political Interest Among Youth During the 2012 Presidential Election: Instructional Opportunities and Challenges in a Swing State. (December 2016) - Levy, Brett L. M.; Solomon, Benjamin G.; Collet-Gildard, Lauren
Political interest is one of the most consistent predictors of political participation, but little research has examined how it develops. This study explores adolescents' political interest development during the 2012 U.S. presidential election. The research team collected and analyzed longitudinal data (surveys, interviews, observations) in high schools located in conservative, liberal, and centrist communities within one swing state. Findings indicate that students' political interest increased during the election. These increases were related to greater public attention to politics and having opportunities to explore multiple sides of political issues and express political opinions. When guiding such experiences, some teachers struggled with various challenges, including one-sided political environments and students' political cynicism. This study has numerous implications for education in democratic societies.